2017
DOI: 10.1080/02699052.2017.1347279
|View full text |Cite
|
Sign up to set email alerts
|

The role of stump pressure and cerebral oximetry in predicting ischaemic brain damage during carotid endarterectomy

Abstract: Objective is to compare the predictive value of stump pressure (SP) and cerebral oximetry (rSO2) levels in the evaluation of ischaemic injury of the cerebrum during clamping of the carotid artery (CCA) without temporary shunt (TS). Methods We included 84 patients with an asymptomatic stenosis (>70%) of the internal carotid artery (ICA) who underwent carotid endarterectomy (CEA) under GA. Cerebral ischaemic tolerance (CIT) was determined on the basis of SP, rSO2 and ∆rSO2 (↓rSO2 from baseline) during CCA. The l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…The level of S100B in TH group was lower compared with the NT group from 6 h after ROSC, while the NSE level was lower in TH group beginning at 24 h after ROSC compared with NT group. These finding were consistent with those of previous studies (19,20). NSE levels have indicated promising results only at later stages (>24 h after cardiac arrest) (21).…”
Section: Discussionsupporting
confidence: 93%
“…The level of S100B in TH group was lower compared with the NT group from 6 h after ROSC, while the NSE level was lower in TH group beginning at 24 h after ROSC compared with NT group. These finding were consistent with those of previous studies (19,20). NSE levels have indicated promising results only at later stages (>24 h after cardiac arrest) (21).…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have found a large increase in S100B levels after declamping [15,16], followed by a reduction in S100B levels 24 hours later [10,17]. Falkensammer [18] investigated the relationship between perioperative levels of the molecular marker S100B and the likelihood of subclinical abnormalities in cerebral function and mild cerebral injury following CEA.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies linked slight cerebral injuies following CEA and a large increase in serum S100B levels [13,14]. Several studies have found a large increase in S100B levels after declamping [15,16], followed by a reduction in S100B levels 24 hours later [10,17]. Falkensammer [18] investigated the relationship between perioperative levels of the molecular marker S100B and the likelihood of subclinical abnormalities in cerebral function and mild cerebral injury following CEA.…”
Section: Introductionmentioning
confidence: 99%